Hospital variation and the impact of postoperative complications on the use of perioperative chemo(radio)therapy in resectable gastric cancer. Results from the Dutch Upper GI Cancer Audit. Issue 4 (April 2018) - Schouwenburg, M.G.; Busweiler, L.A.D.; Beck, N.; Henneman, D.; Amodio, S.; van Berge Henegouwen, M.I.; Cats, A.; van Hillegersberg, R.; van Sandick, J.W.; Wijnhoven, B.P.L.; Wouters, M.W.J.; Nieuwenhuijzen, G.A.P.; et al.
Abstract: Background: Dutch national guidelines on the diagnosis and treatment of gastric cancer recommend the use of perioperative chemotherapy in patients with resectable gastric cancer. However, adjuvant chemotherapy is often not administered. The aim of this study was to evaluate hospital variation on the probability to receive adjuvant chemotherapy and to identify associated factors with special attention to postoperative complications. Methods: All patients who received neoadjuvant chemotherapy and underwent an elective surgical resection for stage IB-IVa (M0) gastric adenocarcinoma between 2011 and 2015 were identified from a national database (Dutch Upper GI Cancer Audit). A multivariable linear mixed model was used to evaluate case-mix adjusted hospital variation and to identify factors associated with adjuvant therapy. Results: Of all surgically treated gastric cancer patients who received neoadjuvant chemotherapy (n = 882), 68% received adjuvant chemo(radio)therapy. After adjusting for case-mix and random variation, a large hospital variation in the administration rates for adjuvant was observed (OR range 0.31–7.1). In multivariable analysis, weight loss, a poor health status and failure of neoadjuvant chemotherapy completion were strongly associated with an increased likelihood of adjuvant therapy omission. Patients with severe postoperative complications had a threefold increased likelihood of adjuvant therapy omission (OR 3.07 95% CI 2.04–4.65). Conclusion: Despite national guidelines, considerable hospital variation was observed in the probability of receiving adjuvant chemo(radio)therapy. Postoperative complications were strongly associated with adjuvant chemo(radio)therapy omission, underlining the need to further reduce perioperative morbidity in gastric cancer surgery.